2019
DOI: 10.1177/2280800018807109
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the light transmission of chairside polymer infiltrated hybrid ceramics in different shades and thicknesses

Abstract: Background: This in vitro study aimed to evaluate the amount of polymerizing light passing through hybrid ceramic specimens in different shades and thicknesses. Methods: Rectangular-shaped feldspathic ceramic computer aided design and computer aided manufacturing (CAD-CAM) blocks and translucent and high translucent polymer infiltrated hybrid ceramic CAD-CAM blocks in four different shades (1M1, 1M2, 2M2, and 3M2) were sectioned in four different thicknesses (0.8, 1.5, 2, and 3 mm), and a total of 48 groups (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
2
8
0
1
Order By: Relevance
“…This effect increases at a faster rate for the zirconia‐based products than for feldspathic ceramic, 25 which might explain the results obtained. Although some studies have described no difference in irradiance among feldspathic and lithium disilicate ceramics, different ceramic shades and methods for assessing irradiance were used, 7,44 which might have influenced the results 16,17,19,21,43,44 . Furthermore, EN also has a feldspathic ceramic network, 28 and yet obtained much lower irradiance compared to the pure feldspathic ceramic (Table 2), as observed in previous findings 21,44 .…”
Section: Discussionmentioning
confidence: 68%
“…This effect increases at a faster rate for the zirconia‐based products than for feldspathic ceramic, 25 which might explain the results obtained. Although some studies have described no difference in irradiance among feldspathic and lithium disilicate ceramics, different ceramic shades and methods for assessing irradiance were used, 7,44 which might have influenced the results 16,17,19,21,43,44 . Furthermore, EN also has a feldspathic ceramic network, 28 and yet obtained much lower irradiance compared to the pure feldspathic ceramic (Table 2), as observed in previous findings 21,44 .…”
Section: Discussionmentioning
confidence: 68%
“…Also, an additional study done by Duran et al in 2019 reported that darker ceramic shades with decreased value transmitted less light than lighter ceramic shades. (20) Specimens with 0.5 mm thickness showed higher degree of conversion of resin cement than 1mm thickness specimens. This may be attributed to the fact that increasing ceramic thickness result in light attenuation by the material thus resin cement receives lower light intensity and incomplete polymerization occurs.…”
Section: Discussionmentioning
confidence: 82%
“…[8] Regardless of the type of cement used (light-cured or dual-cured), the irradiance reaching the luting material is crucial in the provision of optimal polymerization and physical properties to the resin materials in a clinically viable time. [9,10] The ceramic inserted between the light-curing unit (LCU) and the resin cement will affect the light reaching the cement, thus reducing the irradiance significantly [11,12], and it could affect the polymerization of the luting agent. [3,9,13] The polymerization process is initiated in photo-cured resins by a photosensitizer that generates free radicals when exposed to light.…”
Section: Introductionmentioning
confidence: 99%